Kunjungan Antenatal Care dintinjau dari Pengetahuan Ibu Hamil Tentang Tanda Bahaya Kehamilan di Puskesmas Batu Aji Kota Batam Tahun 2019 - Ika Novita Sari (Sehat MasadaJurnal, 2021)
Every pregnancy can have the potential and carry risks for the mother to cause the death of both mother and child, therefore, early detection by health personnel and the community is the key to success in reducing the mortality rate for mothers and babies born to them. The purpose of this study was to determine the relationship between the knowledge of pregnant women about the danger signs of pregnancy. This study used a cross sectional method with 35 respondents as respondents. Statistical analysis using the chi square test. The results showed that the majority of pregnant women made appropriate antenatal care visits as many as 80% and the majority of pregnant women had good knowledge as much as 54.3% and there was a relationship between the knowledge of pregnant women about the danger signs of pregnancy with antenatal care visits at Batu Aji Health Center, Batam City with a p value of 0.002.